2017
DOI: 10.1007/s00404-017-4334-8
|View full text |Cite
|
Sign up to set email alerts
|

Single bolus low-dose of ketamine does not prevent postpartum depression: a randomized, double-blind, placebo-controlled, prospective clinical trial

Abstract: Intra-operative low-dose ketamine (0.25 mg/kg) does not have a preventive effect on postpartum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 29 publications
2
48
0
9
Order By: Relevance
“…Fluoxetine, a traditional antidepressant targeting serotonin reuptake inhibition, is used as treatment for depression including that of women with PPD ( 24 26 ) and requires at least 3 weeks to take effect ( 27 ). Other antidepressants like ketamine may have limited preventative benefits in PPD ( 28 ). On postnatal day 28 after fluoxetine administration for 3 weeks, behavioral tests confirmed the reversal of depressive-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine, a traditional antidepressant targeting serotonin reuptake inhibition, is used as treatment for depression including that of women with PPD ( 24 26 ) and requires at least 3 weeks to take effect ( 27 ). Other antidepressants like ketamine may have limited preventative benefits in PPD ( 28 ). On postnatal day 28 after fluoxetine administration for 3 weeks, behavioral tests confirmed the reversal of depressive-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews evaluating efficacy of postpartum use of selective serotonin reuptake inhibitors (SSRIs) suggest that these drugs are no more effective than placebo in mothers by 3-6 months postpartum (Yonkers et al, 2008;De Crescenzo et al, 2014). Other antidepressants like ketamine (Xu et al, 2017) may have limited preventative benefits in the postpartum. Nonetheless, approximately 6% of mothers use antidepressants after childbirth (Smolina et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…9 Not all studies of ketamine and postoperative depressive symptoms have revealed therapeutic benefit. Intraoperative administration of subanaesthetic ketamine did not prevent postpartum depression in a randomised controlled trial of parturients undergoing Caesarean section (n¼330), 14 although the pathophysiology of this condition is likely distinct as compared with that of a major depressive disorder or depressive symptoms after non-obstetric surgery. Ketamine has also been explored as an adjunct to electroconvulsive therapy that could possibly mitigate adverse cognitive outcomes and improve therapeutic efficacy, but a multicentre trial testing this possibility did not find strong evidence of benefit.…”
mentioning
confidence: 99%